2020
DOI: 10.14336/ad.2019.0402
|View full text |Cite
|
Sign up to set email alerts
|

Roles and Functions of Exosomal Non-coding RNAs in Vascular Aging

Abstract: Aging is a progressive loss of physiological integrity and functionality process which increases susceptibility and mortality to diseases. Vascular aging is a specific type of organic aging. The structure and function changes of endothelial cells (ECs) and vascular smooth muscle cells (VSMCs) are the main cause of vascular aging, which could influence the threshold, process, and severity of vascular related diseases. Accumulating evidences demonstrate that exosomes serve as novel intercellular information comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 139 publications
0
26
0
2
Order By: Relevance
“…LncRNAs frequently reported to regulate to cell apoptosis, angiogenesis and inflammation by has been be involved in post-stroke neuroprotection ( Liang et al, 2020 ). LncRNAs also played a pivotal role in the regulation of vascular smooth muscle cells phenotype, functions, perhaps in the development of vascular aging related heart diseases ( Ni et al, 2020 ). Regulation of cell apoptosis, angiogenesis and inflammation by lncRNAs has been frequently reported to be involved in post-stroke neuroprotection ( Qian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs frequently reported to regulate to cell apoptosis, angiogenesis and inflammation by has been be involved in post-stroke neuroprotection ( Liang et al, 2020 ). LncRNAs also played a pivotal role in the regulation of vascular smooth muscle cells phenotype, functions, perhaps in the development of vascular aging related heart diseases ( Ni et al, 2020 ). Regulation of cell apoptosis, angiogenesis and inflammation by lncRNAs has been frequently reported to be involved in post-stroke neuroprotection ( Qian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that miRNA-233 transforms SMCs from contractile phenotype to synthetic phenotype and promotes VC (82). Other miRNAs with similar effects include miRNA-712, miRNA-714, and miRNA-762 (83). In contrast, miRNA-26a inhibits the differentiation of SMCs, and miRNAs that regulate similar effects of phenotypic transformation by targeting SMAD1 and SMAD4 include miRNA-29a/b and miRNA-125b (83,84).…”
Section: Exosomal Mirnas Regulate Vcmentioning
confidence: 99%
“…Vascular aging involves phenotypic and structural changes in the vascular wall, which consist mainly of endothelial cells and vascular smooth muscle cells. Studies have found the involvement of various exosomal miRNAs and long non-coding RNAs in EC proliferation, inflammation, angiogenesis, senescence, and apoptosis [ 92 ]. For instance, cardiomyocyte-derived exosomal miR-17, miR-19, and miR-126 promoted the proliferation and migration of ECs, whereas miR-92a, miR-24, and miR-21 inhibited the processes [ 93 ].…”
Section: Other Age-related Pathologiesmentioning
confidence: 99%
“…Exosomal miR-125a and miR-106b-5p promote and inhibit angiogenesis, respectively [ 95 ]. Exosomes play a critical role in transferring signaling molecules between ECs and VSMCs and thereby modulate vascular aging [ 92 ].…”
Section: Other Age-related Pathologiesmentioning
confidence: 99%